Integration of Youth in Cyber Traditional Chinese Medicine : A Study on the Construction of Risk Discourse, Behavioral Evolution, and Affordance Pathways in Artificial Intelligence Generated Content - Huang, Junyang; Gao, Zhenghan; Zhang, Yilin (The Journal of Medicine, Humanity and Media, 2025)
Traditional Chinese Medicine(TCM) health preservation is increasingly showing trends of being younger and digitalized. This article analyzes 67 high-interaction TCM health preservation posts published by users aged 18-30 on the rednote platform, based on risk society theory and textual analysis methods, exploring the cognitive dimensions of youth regarding TCM health preservation and its interactive mechanisms empowered by Artificial Intelligence Generated Content(AIGC) technology. The study finds that young people embed TCM health preservation into their daily lives through embodied experiences like Ba Duan Jin (Eight Pieces of Brocade) and health preservation tea, constructing trust in the comprehensiveness of TCM diagnosis with frequent phrases such as 'there are no secrets before TCM', and reinforcing identity and cultural belonging through traditional cultural symbols. In the age of digital intelligence, AIGC technology can promote the digital dissemination of TCM through three pathways: inheritance of embodied skills based on motion capture and VR/AR, intelligent diagnostic systems that enhance health management efficiency, and creative reinterpretation of cultural symbols. This article provides actionable solutions for the digital inheritance and dissemination of TCM health preservation, helping the TCM culture break through generational and media barriers.